2018
DOI: 10.1016/j.preghy.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of sFlt-1/PlGF ratio test in pre-eclampsia prediction and diagnosis in two Brazilian hospitals

Abstract: The sFlt-1/PlGF ratio test has the potential to improve clinical decision-making and allocation of scarce resources by reducing unnecessary hospitalization of women at low risk of developing pre-eclampsia, and ensuring that women at higher risk are identified and managed appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…In this study, we have shown a modest cost‐saving in comparison with other studies . Previous health economic studies of the implementation of PlGF testing in clinical care were based on hypothetical assumptions of reduction in resource use, with greater cost‐savings than we have presented in this analysis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In this study, we have shown a modest cost‐saving in comparison with other studies . Previous health economic studies of the implementation of PlGF testing in clinical care were based on hypothetical assumptions of reduction in resource use, with greater cost‐savings than we have presented in this analysis.…”
Section: Discussionmentioning
confidence: 58%
“…National guidelines have approved PlGF testing to rule out suspected pre‐eclampsia in the UK . Hypothetical economic models have found that PlGF‐based testing gives a cost‐saving of between £330 and £1032 per woman tested . These models have not examined trial data where use of PlGF has been incorporated into clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…PlGF, placental growth factor; PROGNOSIS, PRediction of short-term Outcomes in preGNant wOmen with Suspected preeclampsIa Study; sFlt-1, soluble fms-like tyrosine kinase-1 addition to its clinical performance. Similar research on the cost analysis of introducing the sFlt-1/PlGF ratio test has been performed using population-level data from PROG-NOSIS in the UK, Italy, Germany, Brazil, Switzerland, and the US [24][25][26][27][28][29][30]. In PROGNOSIS, the sFlt-1/PlGF ratio has been shown to improve the short-term prediction of preeclampsia in women with clinical suspicion of the condition, and NICE guidelines recommend the use of the sFlt-1/ PlGF ratio test to rule out preeclampsia, in addition to standard care, in women between 20 and 34 weeks + 6 days of gestation [35].…”
Section: Discussionmentioning
confidence: 99%
“…The economic impact of implementing the sFlt-1/PlGF ratio test, based on PROGNOSIS data, has been assessed in the UK, Italy, Brazil, Germany, Switzerland, and the US [24][25][26][27][28][29][30]. The authors concluded that introducing the test into clinical practice for women with suspected preeclampsia would provide cost savings for the respective healthcare providers, mainly due to the increased ability to rule out preeclampsia and thereby reduce unnecessary hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…59 Other studies show similar findings. [60][61][62][63][64] These recent studies should also be compared with the findings…”
Section: Health Economicsmentioning
confidence: 96%